Filsafat Eksistensialisme Dalam Pandangan Soren Aabye Kierkegaard Terhadap Spiritualitas Pada Remaja Akhir Generasi Z - Herlis Djawa Rama Awang; Difly Praise Malelak (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Existentialism is a school of philosophy that emphasizes individual existence, freedom, and personal responsibility. Soren Kierkegaard, a 19th century philosopher, is considered one of the main figures in the development of this school. In Kierkegaard's view, spirituality is an important aspect of human life, he emphasized the importance of an individual's relationship with God and how this will affect individual existence and freedom. This research uses a qualitative approach by applying library studies or primary data used are books and texts that contain thoughts from Kierkegaard about existentialism and the transformation of self-identity. In late adolescents of generation Z, Kierkegaard's view of spirituality can provide an understanding of the importance of a meaningful life and having a clear purpose. Existentialism can help Generation Z late adolescents to understand and face the existential challenges faced by Generation Z late adolescents, such as finding the meaning of life, facing certainty, and determining their identity.